Answer:
A
Step-by-step explanation:
Formula is y=(x-h) Where h is the number the function is moved left or right...since it is supposed to be moved right, then (x-9) should probably work
Point E is the correct answer! :D
Answer:
apple
Step-by-step explanation:
apple
Answer:
5 & 1
Step-by-step explanation:
We can use the quadratic formula to solve this:
Quadratic Formula = ![\frac{-b+-\sqrt{b^2-4ac} }{2a}](https://tex.z-dn.net/?f=%5Cfrac%7B-b%2B-%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D)
So we will have 2 answers (roots).
a is the coefficient of x^2 (2)
b is the coefficient of x (-12)
c is the constant (10)
Now, substituting, we get:
x = ![\frac{-b+-\sqrt{b^2-4ac} }{2a}=\frac{12+-\sqrt{(-12)^2-4(2)(10)} }{2(2)}=\frac{12+-\sqrt{64} }{4}=\frac{12+-8}{4}=\frac{12+-8}{4}=5,1](https://tex.z-dn.net/?f=%5Cfrac%7B-b%2B-%5Csqrt%7Bb%5E2-4ac%7D%20%7D%7B2a%7D%3D%5Cfrac%7B12%2B-%5Csqrt%7B%28-12%29%5E2-4%282%29%2810%29%7D%20%7D%7B2%282%29%7D%3D%5Cfrac%7B12%2B-%5Csqrt%7B64%7D%20%7D%7B4%7D%3D%5Cfrac%7B12%2B-8%7D%7B4%7D%3D%5Cfrac%7B12%2B-8%7D%7B4%7D%3D5%2C1)
Hence the roots are 5 & 1